Survival outcomes after treatment of cancer of the oral cavity (1985–2015). (March 2019) - Zanoni, Daniella Karassawa; Montero, Pablo H.; Migliacci, Jocelyn C.; Shah, Jatin P.; Wong, Richard J.; Ganly, Ian; Patel, Snehal G.
Highlights: 2082 patients with OSCC operated at a tertiary cancer care center from 1985 to 2015 were studied. Age, comorbidity, margin, vascular and perineural invasion, T, N were independent predictors of OS. Alcohol use, margin, vascular and perineural invasion, T, and N were independent predictors of DSS. pN was the single most powerful and consistent predictor of outcome in patients with OSCC. Abstract: Objectives: To present treatment results of oral squamous cell carcinoma (OSCC) at a tertiary cancer care center from 1985 to 2015. Materials and methods: A total of 2082 patients were eligible for this study. Main outcomes measured were overall survival (OS) and disease specific survival (DSS). Prognostic variables were identified with bivariate analyses using Kaplan-Meier curves and log-rank testing for comparison. A p-value < 0.05 was considered statistically significant and significant factors were entered into multivariate analysis. Median age was 62 years (16–100), 56% were men, 66% reported a history of tobacco use and 71% of alcohol consumption. The most common subsite was tongue (51%). Seventy-three percent of patients had cT1-2 and 71% had clinically negative necks (cN0). Surgery alone was performed in 1348 patients (65%), adjuvant postoperative radiotherapy in 608 patients (29%) and postoperative chemoradiation in 126 patients (6%). Neck dissection was performed in 920 patients with cN0, and in 585 patients with a clinically involved neck. The median follow-up was 37.6 months (range 1–382). Results: The 5-year OS and DSS were 64.4% and 79.3%, respectively. Age, comorbidities, margin status, vascular invasion, perineural invasion, AJCC 8th edition pT, and pN were independent prognostic factors of OS (p < 0.05). History of alcohol consumption, margin status, vascular invasion, perineural invasion, pT, and pN were independent prognostic factors of DSS (p < 0.05). Conclusion: pN stage is the most powerful and consistent predictor of outcome in patients with OSCC treated with primary surgery and appropriate adjuvant therapy.